2010
DOI: 10.1144/sp331.14
|View full text |Cite
|
Sign up to set email alerts
|

Pore structure and durability of Portuguese limestones: a case study

Abstract: Exposed stone surfaces containing complex systems of pores, fractures and grain boundaries provide the surfaces where chemical, physical and biological deterioration processes take place. The pore space represents the preferred area for physical, chemical and biological weathering processes. It plays a significant role in the behaviour of porous materials. A full understanding of pore-channel network morphology, size and connectivity is important in stone decay assessment and conservation works. A contribution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Gauri and Bandyopadhyay present an equation that relates crystallisation pressure of a given salt to porosity of the stone (considering also the volume of the sample, salt absorption and characteristics of the salt such as molar volume, solubility and density). Several laboratory studies have found that higher porosity would promote lower durability in limestones (Skoulikidis et al 1996;Birginie 2000;Nicholson 2001;Cardell et al 2003;Figueiredo et al 2010b) as well as on other rocks such as marbles (Skoulikidis et al 1996) and granites (Rivas et al 2000;Sousa et al 2005). However, some authors have found lower porosity stones presenting lower durability.…”
Section: Introductionmentioning
confidence: 99%
“…Gauri and Bandyopadhyay present an equation that relates crystallisation pressure of a given salt to porosity of the stone (considering also the volume of the sample, salt absorption and characteristics of the salt such as molar volume, solubility and density). Several laboratory studies have found that higher porosity would promote lower durability in limestones (Skoulikidis et al 1996;Birginie 2000;Nicholson 2001;Cardell et al 2003;Figueiredo et al 2010b) as well as on other rocks such as marbles (Skoulikidis et al 1996) and granites (Rivas et al 2000;Sousa et al 2005). However, some authors have found lower porosity stones presenting lower durability.…”
Section: Introductionmentioning
confidence: 99%
“…This was related to difficulties in performing the capillary imbibition tests on the travertine specimens, as explained by the heterogeneous character of this rock type (limiting the access of solutions to the pore space of these limestone specimens). Figueiredo et al (2010 a , 2010 b ) highlighted the positive association of mass loss with porosity in these grainstones, as well as the influence of textural heterogeneities (specially in Moca Creme). In the analyses of the macroscopic erosion patterns of the specimens and following the terminology of Angeli et al (2007), Alves et al (2009) indicated that these grainstones presented a generally homogeneous decay behavior with overall erosion of edges and corners (shape controlled), whereas the travertine sample showed heterogeneous patterns that these authors related to the presence of clay minerals.…”
Section: Discussionmentioning
confidence: 94%
“…The grainstones are from a Bathonian (Middle Jurassic) formation [Direcção-Geral de Geologia e Minas (DGGM), 1983–1985; Instituto Geológico e Mineiro (IGM), 1995; Manuppella et al, 1985] located about 100 km north of Lisbon (Portugal). These grainstones are classified (Figueiredo et al, 2010 a , 2010 b ) as fossiliferous pelmicrosparite/grainstone (Semi-rijo samples) and as biopelintrasparite/grainstone (Moca Creme samples). Semi-rijo presents rare rounded bioclasts (allochemical components size ranging from 0.08 to 1.6 mm), whereas Moca Creme is richer in bioclasts and has a coarser texture with pelloids ranging from 0.03 to 0.08 mm and bioclasts with, in general, a centimetric size.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Limestone supported walls of faience tiles also suffer from salts crystallization. Salts may be carried into the stone with groundwater by capillary rise (Figueired et al, 2010) or may be dissolved from the mortar joints, or result from chemical reaction between atmospheric pollutants (especially SO2) and minerals (such as calcite (CaCO3) in the limestone). If salts precipitated beneath the material of surface (a phenomenon called subflorescence or cryptoflorescence) severe damage can be induced (Espinosa-Marzal et al, 2010).…”
Section: Causes Of Decay Of Faience Tilesmentioning
confidence: 99%